Standardized classification schemes in reporting oncologic PET/CT - Murad, Vanessa; Kulanthaivelu, Roshini; Ortega, Claudia; Veit-Haibach, Patrick; Metser, Ur (Frontiers in Medicine, 2023)
The imaging report is essential for the communication between physicians in patient care. The information it contains must be clear, concise with evidence-based conclusions and sufficient to support clinical decision-making. In recent years, several classification schemes and/or reporting guidelines for PET have been introduced. In this manuscript, we will review the classifications most frequently used in oncology for interpreting and reporting 18F-FDG PET imaging in lymphoma, multiple myeloma, melanoma and head and neck cancers, PSMA-ligand PET imaging for prostate cancer, and 68Ga-DOTA-peptide PET in neuroendocrine tumors (NET).